Simultaneous Transmission and Reflection Beamforming Design for RIS-Aided MU-MISO - Lin, Yuming; Shen, Yuanjun; Li, Ang (IEEE transactions on vehicular technology, 2023)
In this paper, we study the beamforming design for the simultaneous transmission and reflection reconfigurable intelligent surface (STAR-RIS) assisted MU-MISO system, where the energy splitting (ES) mode is adopted for STAR-RIS. We aim to jointly design the beamforming strategy at the BS and the transmission-reflection coefficients (TRCs) at the STAR-RIS to minimize the total downlink transmit power of the base station (BS) subject to each user's SINR constraint. The formulated optimization problem is difficult to solve directly, and therefore we employ the iterative alternating optimization (AO) framework to obtain suboptimal solutions with promising performance. Specifically, we propose an AO-based solution to optimize each amplitude and phase of the TRCs at the STAR-RIS separately in a sequential manner, where two distinct approaches are introduced for the design of the amplitudes of STAR-RIS elements. Simulation results show that the proposed joint beamforming design at BS and passive design at STAR-RIS achieves a promising performance, and requires fewer iterations compared with the state-of-the-art.